Values Related to the Religious Adherence - Janek Musek (Psychological Topics, 2017)
The religions and their value systems play a crucial role in the history of human civilization. In the past and in the recent time, the value-based religious differences substantially contribute to the societal conflicts. Thus, the research of the values related to the religious orientation is an important task of psychology and other social sciences. This study is aimed to obtain a more complete insight into the differences in the value orientations between the adherents of the seven major religions in the world: Buddhist, Hindu, Jewish, Muslim, Christian Orthodox, Christian Protestant and Christian Catholic. The results clearly demonstrated, (1st), the essential association of the religious or non-religious beliefs with the values, value priorities and value orientations and, (2nd), the substantial differences between religious or non-religious groups in the value systems. These differences are very probably related to the globally observed distinctions between secularism and fundamentalism and underlying ideological and educational doctrines.